Botany in Hawaiʻi - Elliott, Daniela Dutra; Velasquez, Paula Mejia (Open textbook library., 2022)
"Botany in Hawai‘i" discusses introductory topics of Botany through examples of the native and introduced plants found in Hawai‘i. It includes anatomy and physiology of seeds, roots, leaves, stems, fruits and flowers and covers the main plant groups from nonvascular to flowering plants. This book provides a visual reference to botanical concepts and terminology for beginners.